Sedimentary Record of Paleogene Sequences in the Penyu and Malay Basins, Offshore Peninsular Malaysia - Franz L. Kessler; John Jong; Mazlan Madon (Berita Sedimentologi, 2020)
The Eocene to Lower Oligocene deposits of the Penyu and Malay basins are formed by fluvial-lacustrine deposits with marine influence in the latter. The sequence consists mainly of siltstone, with several intercalations of fine-grained sand and volcanic tuff. Based on well data, Mid-Upper Eocene sediments exist in Penyu Basin in the deeper parts of the half grabens and sub-basins. Hence, this implies the age of basin initiation at Mid-Eocene, rather than Oligocene as traditionally and commonly stated in the literature. By correlation, and as seismic evidences show, Eocene sediments also appear to exist in the deeper, undrilled parts of the Malay Basin, again implying that at the latest, a Mid-Eocene age of basin initiation.In the Penyu Basin, aprominent near-Base Oligocene Unconformity can potentially be correlated to the Base-Tertiary Unconformity in the adjacent Malay Basin, however the latter term implies all Tertiary sequences, including potential Paleogene deposits above the unconformity. Besides, we also observe intra-Eocene unconformities, called the Top N and Top O. The presence of Eocene strata is likely associated with an early phase of extensional tectonism, and probably related to the onset of rifting of the South China Sea continental crust.